Advancing rigour in solicited diary research. (August 2018) - Filep, Crystal Victoria; Turner, Sarah; Eidse, Noelani; Thompson-Fawcett, Michelle; Fitzsimons, Sean
Solicited diaries/journals are increasingly popular as an innovative qualitative method in the social sciences for better understanding people's everyday lived experiences. In this article we create a framework for maintaining rigour while using such diaries. First, we systematically evaluate 43 research papers focusing on the method, drawing on Baxter and Eyles' (1997) seminal evaluation of rigour in qualitative human geography research. We ascertain that significant improvements could be made to procedures for obtaining and analysing diary content. Second, we develop a framework to encourage rigour in diary research. We test our framework by evaluating research conducted by two of our authors who employed solicited diaries with street vendors in Vietnam. We propose that our analysis and framework can help social scientists improve the rigour of solicited diaries as a research method, and provide a model for enhancing rigour in other emerging qualitative approaches.